2023
DOI: 10.1039/d3mh00625e
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating defogging metasurfaces via a water-based colloidal route

Abstract: Metamaterials possess exotic properties that do not occur in nature and have attracted significant attention in research and engineering. Two decades ago, the field of metamaterials emerged from linear electromagnetism,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…For example, Akselrod et al 31 demonstrated the use of colloidal synthesis to create large-area metasurfaces, paving the way for scalable and cost-effective fabrication methods. Additionally, Khoruzhenko et al 32 detailed the preparation of colloidal metasurfaces with tunable optical properties, while Petronella et al 33 demonstrated the dynamic tuning capabilities of liquid crystal-integrated metasurfaces. Lastly, Kim et al 34 introduced a hierarchical doping strategy to enhance the optical response of nanocrystal-based metasurfaces.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, Akselrod et al 31 demonstrated the use of colloidal synthesis to create large-area metasurfaces, paving the way for scalable and cost-effective fabrication methods. Additionally, Khoruzhenko et al 32 detailed the preparation of colloidal metasurfaces with tunable optical properties, while Petronella et al 33 demonstrated the dynamic tuning capabilities of liquid crystal-integrated metasurfaces. Lastly, Kim et al 34 introduced a hierarchical doping strategy to enhance the optical response of nanocrystal-based metasurfaces.…”
Section: ■ Introductionmentioning
confidence: 99%